Phytochemical, Biological, Stability And Pharmacokinetic Studies On The Extracts Of Three Varieties Of Ficus Deltoidea Jack Leaves - Abdullah, Zunoliza (2010)
This study has been conducted to provide information on the standardization of extracts of Ficus deltoidea (FD) leaves. Three plant varieties namely FD var. terengganuensis, FD var. angustifolia and FD var. deltoidea were studied. The study was divided into five parts: chemical investigation, chemical profiling, biochemical profiling, stability studies and biological profiling.Five compounds have been isolated that includes three triterpenoids, β-amyrin cinnamate, β-sitosterol and friedelin and two flavonoids, vitexin and isovitexin. Identification and structural elucidation of these compounds was established through spectroscopic techniques.